Perinatal Outcome in Patients with Borderline AFI - Salma Sadia, Nishat Akram, Sana Gull, Hina Aftab, Muhammad Athif Akram, Rehana Kanwal, Hafiz Irfan Shahzad, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: During pregnancy, amniotic fluid indicates the normal placental function. It is the most essential element for surveillance of fetal growth and health. Amniotic fluid index (AFI) is the most ideal way to determine the level of amniotic fluid during pregnancy. However, the single deepest pocket is applied to determine the changes in AFI level in pregnancies suspected to oligohydramnios. Borderline AFI is defined as AFI levels > 5 to < 10cm; it is a challenging task in obstetrics to associate it with adverse pregnancy outcomes. Objective: To assess the perinatal outcomes in patients with borderline AFI. Study Design: Cross-sectional. Setting: Department of Obstetrics & Gynaecology, Sharif Medical City Hospital, Lahore. Study Duration: Study was carried out over a period of six months from 10-11-2020 to 11-05-2021. Subjects And Methods: A total of 160 patients having borderline AFI (more than 5 and less than 10cm) were included in the study. Perinatal outcomes were assessed at the time of delivery in the hospital. Data Analysis Method: Stratification of data was carried out with regard to age, gestational age, parity and area of residence. Results: Mean age of the patients was 25.17±4.90 years. Mean gestational age was observed to be 38.44±1.54 weeks. Majority of the patients were between Para 0 to 3. There was no smoker in preset study. Most of the patients belonged to rural area. Perinatal outcomes were as follows: Intrapartum fetal distress was observed in 64 (40%), meconium staining in 56 (35%), Apgar score < 10 at 5 minutes in 37 patients (23.1%) and NICU admission in 38 (23.8%). Conclusion: In conclusion, borderline AFI during pregnancy can lead to severe hazardous consequences. Therefore, pregnancy complicated with borderline AFI must be observed carefully in order to improve the outcome of pregnancy and avoid adverse perinatal outcomes. Keywords: Borderline AFI, Apgar Score, NICU Admission, Intrapartum Fetal Distress, Meconium Staining.